2016
DOI: 10.3906/zoo-1506-7
|View full text |Cite
|
Sign up to set email alerts
|

Developmental differences of local populations of alfalfa weevil (Hypera postica) (Coleoptera: Curculionidae)

Abstract: Many invasive insect pests show phenotypic variation between local populations across their geographical range. Understanding and integrating such differences will help to improve pest management. Population differences are the result of local adaptation to environmental conditions and may be detected using ecological analyses. Immature stages may represent especially interesting study objects as they represent important stages in the life cycle of insects and in many cases may be the most destructive stage. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
4
1
Order By: Relevance
“…Although, at low temperatures, very few eggs of H. postica hatched at humidity levels below 95% in a previous study [ 30 ], our results showed that nearly 50% of the eggs survived at a low RH regime. The differences between our results and others from North America or Middle East could be due to differences between regional populations [ 19 , 21 ], as has been reported when the influence of temperature in the postembryonic development of H. postica was studied [ 14 , 18 ].…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Although, at low temperatures, very few eggs of H. postica hatched at humidity levels below 95% in a previous study [ 30 ], our results showed that nearly 50% of the eggs survived at a low RH regime. The differences between our results and others from North America or Middle East could be due to differences between regional populations [ 19 , 21 ], as has been reported when the influence of temperature in the postembryonic development of H. postica was studied [ 14 , 18 ].…”
Section: Discussioncontrasting
confidence: 75%
“…However, our results differ from those of these authors because a high proportion of eggs hatched even at a medium and low HR. (3) The survival of eggs was higher at a medium RH at middle-high temperatures (24, 28, and 32 °C), indicating that a globally medium RH is the best regime for egg hatching for Spanish populations of H. postica, which was also observed in studies done with populations from the Asian Middle East [ 14 , 19 ].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Several factors may have contributed to the mitochondrial lineage divergence and diversification in H. postica ; these may include population history, adaptation to different hosts, or disrupted interpopulation gene flow (Iwase, Nakahira, et al, ; Iwase, Tani, et al, ; Sanaei & Seiedy, ; Sanaei, Seiedy, & Momtazi, ; Sanaei et al, ). One additional potentially important agent is the intracellular alpha‐proteobacteria Wolbachia (Hertig, ; Werren, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, geometric morphometric analyses showed that the Jovein population has significant differences in pronotum shape compared to other Iranian populations (Sanaei et al 2015b). In addition, the separation of the eastern population (Jovein) from other western populations was observed in some important ecological aspects (Sanaei and Seiedy, in press): immature life stage analysis indicated that the pupal stage of the Jovein population is one day longer than in the western populations (Sanaei and Seiedy, in press). Our mitochondrial data is compatible with these previous morphometric and life table data, but cannot support them strongly (Table 3).…”
Section: Discussionmentioning
confidence: 99%